TREATMENT OF ACUTE RESPIRATORY DISTRESS SYNDROME - Ferreira, Gledja Akythiara de Araújo; dos Santos, Gabriel Evangelista; Oliveira, Amanda dos Santos; Vicente, Nicolas Schafer; Diniz, Yngryson Almeida; Góis, Lucas Jaffé de Carvalho; da Silva, Mike Draiher; de Vasconcelos, Catarina Cursino; Grasso, Isabela Vitória; Loureiro, Helena Bicalho; Bazana, Gustavo Stanislaski; Leitão, Ana Beatriz Peixoto (Seven Editora, 2026)
Acute Respiratory Distress Syndrome (ARDS) remains a significant cause of severe respiratory failure in intensive care units, associated with high mortality and marked clinical, pathophysiological, and biological heterogeneity. This chapter aimed to review the most recent scientific evidence on the treatment of ARDS, with an emphasis on protective ventilatory strategies and individualized therapeutic approaches. This is a narrative literature review, conducted in the PubMed database, including articles published in the last five years directly related to the management of the syndrome. The analyzed evidence demonstrates that invasive mechanical ventilation with low tidal volumes, plateau pressure limitation, careful PEEP titration, prolonged prone positioning, and selective use of neuromuscular blocking agents remain the cornerstones of treatment. In addition, rescue therapies, such as ECMO, and non-invasive strategies can be employed in specific situations. Recent literature also highlights the relevance of phenotypic stratification, multimodal monitoring, and advanced imaging tools, such as electrical impedance tomography, for individualizing ventilatory support and reducing ventilator-induced lung injury. It is concluded that contemporary ARDS management should integrate established protocols with personalized approaches, guided by biological phenotypes, functional monitoring, and early rehabilitation, aiming to optimize clinical outcomes and functional recovery of patients.